Acute Alcohol Toxicity. Issue 2 (June 2014) - Morley, Stephen R.; Smith, Paul; Johnson, Christopher
Acute alcohol (ethanol) toxicity is a definition that encompasses both the metabolic toxicity of alcohol and the association of alcohol with traumatic deaths, suicide, and criminal activities. As with any postmortem measurement, there must be control of postmortem sampling, storage of specimens, and appropriate analysis to ensure that there is not artifactual alcohol production or incorrect measurement of other postmortem alcohols. It is almost unheard of for acute alcohol toxicity to cause death secondary to metabolic effects in a naïve individual, although there has been a recent trend in social media dares that have led to deaths due to isolated episodes of extreme alcohol consumption. However, in most cases, there will be evidence for chronic alcohol misuse at the postmortem examination.